2021
DOI: 10.1108/jiabr-06-2020-0194
|View full text |Cite
|
Sign up to set email alerts
|

Market discipline in the behavioral finance perspective: a case of Sharia mutual funds in Indonesia

Abstract: Purpose This study aims to determine antecedents of market discipline. A model was constructed by extending the theory of planned behavior (TPB) to explore the cognitive, psychological and social factors that influence the market discipline in the form of withdrawal behavior. Design/methodology/approach This study applied a quantitative approach by surveying 181 Indonesian retail investors in Sharia mutual funds, which were represented by civil servants. The samples were collected using the purposive samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 79 publications
(107 reference statements)
5
20
1
Order By: Relevance
“…The regression weight of FB of 0.452 indicates that the direct contribution of FB on MD is about 45.2%. The result is consistent with Soma et al (2016) and Widyastuti et al (2022), who also find the positive effect of financial literacy on market discipline.…”
Section: Indicators Statementssupporting
confidence: 92%
See 3 more Smart Citations
“…The regression weight of FB of 0.452 indicates that the direct contribution of FB on MD is about 45.2%. The result is consistent with Soma et al (2016) and Widyastuti et al (2022), who also find the positive effect of financial literacy on market discipline.…”
Section: Indicators Statementssupporting
confidence: 92%
“…As a result, in this study, market discipline emphasized depositor withdrawal behavior, which reflects a lack of information disclosure that market participants could use to supervise banks' risk and capital profiles. Market discipline by depositors has been extensively studied from the finance behavioral perspective in the non-bank sector by Soma et al (2016) and Widyastuti et al (2022). The current study contributes to filling the theoretical gap by exploring market discipline as it applies in banking.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The impact of perceived financial risk toward tourist satisfaction and visit intention Widyastuti et al (2021) underlined the significant and negative impact that perceived financial risk had toward individual's intention in purchasing certain products. Similarly, Dash (2020) also found that consumers' intention to visit certain places will increase when they perceive that there won't be any kinds of risks which might cause them financial loss from the transactions.…”
Section: 5mentioning
confidence: 99%